The Effect of Uno Block Playing Therapy on Improving Cognitive Function in Elderly People with Dementia - Yuli Yanti; Astri Febrina Fatmawati; ST Budi Yuwono (GLOBAL HEALTH SCIENCE GROUP, 2025)
Elderly individuals with dementia experience a decline in cognitive function, which affects their independence and daily quality of life. Uno Block play therapy is a form of cognitive and social stimulation that involves arranging and moving numbered and colored blocks according to specific rules. This activity stimulates memory, attention, fine motor coordination, and social interaction. This study aims to analyze the effect of Uno Block play therapy on the cognitive function of elderly patients with dementia at PSTW Budi Mulia 3 Jakarta. Method: The study used a quasi-experimental design with a pretest–posttest control group involving 32 elderly participants. They were selected using purposive sampling based on the following inclusion criteria. Participants were divided into an intervention group (n = 16) and a control group (n = 16). Cognitive function was measured using the Mini-Mental State Examination (MMSE), and data were analyzed using the Wilcoxon test for non-normally distributed paired data. The results showed a significant difference in cognitive function scores before and after the intervention in the intervention group (p = 0.005), while no significant difference was observed in the control group (p = 0.157). It can be concluded that Uno Block play therapy has a significant effect on improving the cognitive function of elderly individuals with dementia.